Penerapan Data Mining Untuk Pengelompokan Minat Konsumen Terhadap Pengguna Jasa Pengiriman Pada PT. Jalur Nugraha Ekakurir (JNE) Pematangsiantar - Rudi Wardana Nasution; Suhada Suhada; Ika Okta Kirana; Indra Gunawan; Ika Purnama Sari (STMIK Budi Darma, 2021)
Datamining is a method for finding knowledge in a large enough data pile by the process of digging and analyzing a very large amount of data in obtaining something that is true, new and useful so that it can be found in a pattern or pattern in the data. Customer service in general is every activity intended or intended to give satisfaction to customers, through this service the wishes and needs of customers can be met. In the Indonesian Dictionary explained that service is an attempt to serve the needs of others, while serving is to help prepare (help what someone needs). essentially service is a series of activities that constitute a process. As the service process takes place routinely and continuously covers the entire life of people in the community, the process of meeting needs through the activities of others including JNE is also a company that offers services engaged in shipping and logistics based in Jakarta, Indonesia. The official name is Tiki Path Nugraha Ekakurir (Tiki JNE) K-Means Algorithm is an iterative clustering algorithm that partitions data sets into a number of K clusters that have been set at the beginning.